195 Work injury risk by time of day in two population-based data sources. (11th October 2013) - Mustard, A; Chambers,; McLeod,; Bielecky,; Smith,
Abstract : Mini-Symposium: Innovative uses of workers' compensation data: improving the impact. Objective: To estimate the rate of work injury over the 24 hour clock in two independent data sources for the Ontario labour force over a five year period 2004–2008. Methods: A cross-sectional, observational study of work-related injury and illness for a complete population of occupationally-active adults 15–64. The two independent data sources were lost-time compensation claims and emergency department encounter records. Estimates of hours worked annually for the Ontario labour force by time of day, age, gender, and occupation were derived from population-based surveys. Results: The incidence of emergency department visits for work-related conditions was approximately 40% higher than the incidence of lost-time workers' compensation claims: 707, 933 emergency department records and 457, 141 lost-time claims. For men and for women and across all age groups, there was an elevated risk of work-related injury or illness in the evening, night and early morning periods in both administrative data sources. This elevated risk was consistently observed across manual, mixed and non-manual occupational groups. The fraction of lost-time compensation claims that can be attributed to the elevated risk of work injury in evening or night work schedules is 12.5% for women and 5.8% for men. Conclusions: Despite the high prevalence of employment in non-daytime work schedules in the developed economies, the work injury hazards associated with evening and night schedules remains relatively invisible. This study has demonstrated the feasibility of using administrative data sources to enhance the capacity to conduct surveillance of work injury risk by time of day. More sophisticated etiologic research is needed to understand the specific mechanisms of hazards associated with non-regular work hours.